Thyroid cancer GWAS identifies 10q26.12 and 6q14.1 as novel susceptibility loci and reveals genetic heterogeneity among populations. Issue 8 (22nd April 2015) - Mancikova, Veronika; Cruz, Raquel; Inglada‐Pérez, Lucía; Fernández‐Rozadilla, Ceres; Landa, Iñigo; Cameselle‐Teijeiro, José; Celeiro, Catuxa; Pastor, Susana; Velázquez, Antonia; Marcos, Ricard; Andía, Victor; Álvarez‐Escolá, Cristina; et al.
<x xml:space="preserve">Abstract</x> Thyroid cancer is the most heritable cancer of all those not displaying typical Mendelian inheritance. However, most of the genetic factors that would explain the high heritability remain unknown. Our aim was to identify additional common genetic variants associated with susceptibility to this disease. In order to do so, we performed a genome‐wide association study in a series of 398 cases and 502 controls from Spain, followed by a replication in four well‐defined Southern European case‐control collections contributing a total of 1, 422 cases and 1, 908 controls. The association between the variation at the 9q22 locus near FOXE1 and thyroid cancer risk was consistent across all series, with several SNPs identified (rs7028661: OR = 1.64, p = 1.0 × 10−22, rs7037324: OR = 1.54, p = 1.2 × 10−17). Moreover, the rare alleles of three SNPs (rs2997312, rs10788123 and rs1254167) at 10q26.12 showed suggestive evidence of association with higher risk of the disease (OR = 1.35, p = 1.2 × 10−04, OR = 1.26, p = 5.2 × 10−04 and OR = 1.38, p = 5.9 × 10−05, respectively). Finally, the rare allele of rs4075570 at 6q14.1 conferred protection in the series studied (OR = 0.82, p = 2.0 × 10−04). This study suggests that heterogeneity in genetic susceptibility between populations is a key feature to take into account when exploring genetic risk factors related to this disease.